Effect of Hibiscus sabdariffa Linn. on the development of atherosclerosis in diabetes mellitus: a rapid review - Fakhrul Gamal Putra; Nurul Paramita; Dewi Irawati Soeria Santoso (Published by Universitas Gadjah Mada, 2025)
Atherosclerosis is closely linked to disturbances in lipid metabolism and chronic inflammation. In diabetes mellitus (DM), hyperglycemia exacerbates atherosclerosis by inducing structural changes in blood vessel endothelium through chronic inflammation triggered by oxidized low-density lipoprotein (OxLDL) formation. Inflammation plays a major role in atherosclerosis pathogenesis, with OxLDL, nuclear factor kappa B (NFkB), intercellular adhesion molecule-1 s(ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) being crucial players in this process. Hibiscus (Hibiscus sabdariffa Linn.) a medicinal plant rich in polyphenols, is believed to have a role to prevent atherosclerosis development through its antioxidant activity, inhibiting vascular smooth muscle cell (VSMC) proliferation, and modulating inflammation pathways. This review explores the potential of hibiscus to prevent atherosclerosis development in DM, focusing on its phytochemical compounds and their impact on oxidative stress, hyperlipidemia, and inflammation pathways. The review highlights the importance of targeting VSMC proliferation, migration, and inflammatory responses mediated by ICAM-1 and VCAM-1 to attenuate atherosclerosis progression. Hibiscus shows promise as a natural treatment for atherosclerosis, but further research is still needed to fully understand its mechanisms and therapeutic potential.